HASTE MRI sequence findings correlate with loss of deep pain perception in dogs with thoracolumbar disc extrusion. Issue 2 (27th October 2022) - Khan, Sam; Freeman, Paul
Abstract: Background: Thoracolumbar intervertebral disc extrusion (TL IVDE) is a common reason for the veterinary hospital admission. Various imaging factors including degree and length of compression have been tested for correlation with clinical severity, but no reliable correlation has been found. Half‐Fourier acquisition single‐shot turbo spin echo (HASTE) magnetic resonance imaging (MRI) sequences highlight the dorsal and ventral cerebrospinal fluid (CSF) columns and have been used to demonstrate spinal cord swelling in dogs with TL IVDE. This has been used as a predictor of progressive ascending‐descending myelomalacia but has not been correlated with neurological grade. Objective: This study aims to investigate the correlation between the attenuation of CSF HASTE signal and clinical severity in dogs suffering from TL disc extrusions. Methods: Dogs less than 15 kg who were non‐ambulatory due to suspected TL IVDE were prospectively recruited for a study into conservative management. MRI studies were undertaken under sedation including HASTE sequences. The ratio of the length of CSF attenuation to the length of the L2 vertebra was calculated and correlated with clinical severity. Results: Twenty dogs met the inclusion criteria. No statistically significant difference was demonstrated between the mean CSF attenuation and neurological grade ( p  = 0.17 but there was a significant difference in the mean CSF attenuation in those who retained deep pain perception and those who did not ( p  = 0.02). Time to loss of ambulation was also found to not be correlated with CSF attenuation ( p  = 0.95). Conclusion: In conclusion, the length of CSF attenuation of HASTE MRI sequences in dogs less than 15 kg suffering from IVDEs may be correlated with a loss of deep pain perception. Abstract : Dogs who were non‐ambulatory due to suspected thoracolumbar intervertebral disc extrusion underwent MRI studies including half‐Fourier acquisition single‐shot turbo spin echo sequences. The ratio of the length of CSF attenuation to the length of the L2 vertebra was calculated and correlated with clinical severity. This showed that the length of CSF attenuation sequences may be correlated with a loss of deep pain perception.